The use of mycorrhizal fungi for growing Zn-enriched lettuce - Kailer, Endy Lopes (2021)
Today, over two billion people face the negative outcomes of micronutrient deficiencies all over the world, especially when it comes to zinc. Agronomic biofortification is considered the most cost-effective way to increase zinc content in food products. Known as the “ecosystem’s invisible engineers”, arbuscular mycorrhizal fungi (AMF) are associated with more than 80% of all the living plants and are responsible for enhancing nutrient uptake. Lettuce (Lactuca sativa L.) is one of the most widely consumed vegetables worldwide and its nutritional value can directly impact the daily nutrient intake of millions of people. In this sense, this research aimed to assess the effect of mycorrhizal inoculation in the biofortification of Zn in lettuce leaves. Thus, lettuce pots were cultivated in a greenhouse in a completely randomized block design experiment in a double factorial design (5x2), composed by five doses of Zn (0, 8, 32, 64, and 96 mg/dm 3 ) as Zn sulphate (ZnSO 4 ) and two levels of mycorrhizal inoculation (presence and absence) in seven replications. Experimental data were subjected to variance (ANOVA) and regression analysis. Regardless of the applied dose, plants that were inoculated with AMF presented an increase in fresh weight of shoots, shoot height, dry matter, root volume and leaf number. Also, the inoculation with AMF did not show any effect on the zinc concentration of the leaves, showing that biofortification may happen regardless of AMF inoculation in lettuce leaves. Plants that were inoculated with AMF showed higher levels of total zinc content per plant, presenting a linear response as Zn fertilization was increased. As inoculated plants grew more, the nutrient suffered tissue dilution effect, as leaves were wider. Dry matter showed a decrease with doses higher than 32 mg/dm 3 , showing some signs of phytotoxicity. Plants were biofortified, accumulating 25 times more Zn in the highest dose when compared to the control ones. Thus, association with AMF can stimulate plant growth and lead to higher zinc content in lettuce leaves. Keywords: Agronomic biofortification. Nutrient uptake. Hidden hunger. Zinc fertilization. Soil microorganisms.